2011
DOI: 10.1039/c0nj00697a
|View full text |Cite
|
Sign up to set email alerts
|

Bis 4,5-diazafluoren-9-one silver(i) nitrate: synthesis, X-ray structures, solution chemistry, hydrogel loading, DNA coupling and anti-bacterial screening

Abstract: Synthesis of bis-4,5-diazafluoren-9-one silver(I) nitrate I, (dafone = 4,5-diazafluoren-9-one) and low temperature X-ray single crystal structure of [Ag(4,5-diazafluoren-9-one) 2 NO 3 ], crystal form 1, and a re-determination of [Ag(4,5-diazafluoren-9-one) 2 ]NO 3 ·H 2 O, crystal form 2 are presented.Crystal form 1 has a distorted trigonal planar coordination geometry around Ag(I) with an N-Ag-N bond angle of 123.45(7)°. Crystal form 2 has a perfect linear coordination around Ag, with N-Ag-N 180.0°. Compound I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…nClO 4 In some related studies the ESI-MS of the silver(I) trifluoromethan sulfonate (AgO 3 SCF 3 ) compound with 3,6-di(2-pyridyl)pyridazine in CH 3 CN were consistent with X-ray crystallography where the same cations [Ag(L) 2 ] + (Ag:L = 1:2) were found [30]. Similarly, the ESI-MS for the compound [Ag(4,5-diazafluoren-9-one) 2 ]NO 3 [21] showed only one strong peak representing the complex [Ag(L) 2 ] + with (Ag: L = 1:2). On the contrary, the ESI-MS for a solution containing AgBF 4 and excess bidentate 1,12-diazaperylene ligand indicate the formation of the 1:1 (90%) Ag:L complex while the expected 1:2 complex is only observed as a minor peak (10%) [31].…”
supporting
confidence: 64%
“…nClO 4 In some related studies the ESI-MS of the silver(I) trifluoromethan sulfonate (AgO 3 SCF 3 ) compound with 3,6-di(2-pyridyl)pyridazine in CH 3 CN were consistent with X-ray crystallography where the same cations [Ag(L) 2 ] + (Ag:L = 1:2) were found [30]. Similarly, the ESI-MS for the compound [Ag(4,5-diazafluoren-9-one) 2 ]NO 3 [21] showed only one strong peak representing the complex [Ag(L) 2 ] + with (Ag: L = 1:2). On the contrary, the ESI-MS for a solution containing AgBF 4 and excess bidentate 1,12-diazaperylene ligand indicate the formation of the 1:1 (90%) Ag:L complex while the expected 1:2 complex is only observed as a minor peak (10%) [31].…”
supporting
confidence: 64%
“…52 It is perhaps significant that these structures, to a varying degree, have Ag…O interactions with a nitrate anion, and that these, and the surrounding crystal packing effects, may play a significant role difficult to model with a simple DFT calculation. In the 4,5-diazafluoren-9-one case there are also two different crystal structures reported, 53 containing two very dissimilar [Ag(4,5-diazafluoren-9-one) 2 ] + complexes. In contrast, but perfectly consistent with this discussion, the almost perfectly linear coordination geometry with negligible nitrate interaction reported by Zhou et al is well reproduce by their DFT calculations.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…168 The in vitro linear dichroism studies also showed that both dafo and the silver complexes bind to calf thymus DNA, however the complexes showed significantly stronger binding to DNA compared with the free ligand. 168 The free 9-diazo-4,5-diazafluorene can be photochemically activated to release dinitrogen as a byproduct and generate a triplet carbene. 169 Matrix photolysis experiments of complex [Cu(9-diazo-4,5-diazafluorene) 2 (NO 3 ) 2 ] (Fig.…”
Section: Iii4 Bioinorganic Chemistry Of 45-diazafluorene Derivativesmentioning
confidence: 95%